Law, Gender and Sexuality at the British Library. (19th March 2015) - Sims, Jonathan
Abstract: This article, by Jonathan Sims, is based on a presentation given at the national training day on Law, Gender and Sexuality: Sources and Methods in Socio-Legal Research in May 2014, jointly sponsored by the Institute of Advanced Legal Studies, the Socio-Legal Studies Association and the British Library. The article identifies library collections and resources which, beyond the scope of typical law collections, might be useful for broadly socio-legal academic research on intersections between law, gender and sexuality.